TOWARDS AN INTERPRETATION OF THE PHENOMENA OF DEMON POSSESSED/DEMONIZED CHRISTIANS - Gani Wiyono (Jurnal Teologi Amreta (ISSN: 2599-3100))
In the pre-modern world people generally believed in the supernatural. Individuals and culture as a whole believed in the existence of God (or gods), angels, and demons. The visible world owed its existence and meaning to a spiritual realm beyond the senses. However, such worldviews began to die with the coming of Enlightenment of 17th and 18th centuries. The age of reason, scientific thinking, and human autonomy that characterized the Enlightenment brought to being the so-called natural religion. The result was the disappearance of immanent God (Deism) and the rejection of the socalled “excluded middle” – the unseen world of spirits, and the supernatural. Such attitude may well be summarized in Rudolf Bultmann’ famous statement: “It is impossible to use electric light and the wireless and to avail ourselves of modern medical and surgical discovers, and at the same time to believe in the New Testament worlds of spirits and miracles.”